A Three‐Layer All‐In‐One Flexible Graphene Film Used as an Integrated Supercapacitor. Issue 11 (10th May 2017) - Du, Jiamei; Zheng, Cheng; Lv, Wei; Deng, Yaqian; Pan, Zhengze; Kang, Feiyu; Yang, Quan‐Hong
Abstract : The electronic devices are becoming smaller, more flexible, and wearable, thus requiring the energy storage unit to have not only high volumetric energy density but also small thickness and high flexibility. Supercapacitors (SCs), as a typical energy storage device, have the advantage of fast energy charging and releasing. The present progress on SCs implies a tremendous need to transform traditional configuration into flexible and thin enough membrane‐like supercapacitors. This work shows a high volumetric energy density membrane‐like flexible supercapacitor with an rGO‐TiO2 /GO/rGO‐TiO2 sandwich structure, in which the rGO‐TiO2 layer is used as the active material and the middle GO layer acts as the separator. The supercapacitor in one compact graphene‐based membrane has shown great flexibility and at the same time guarantees a high volumetric capacity of 237 F cm −3 and a high volumetric energy density of 16 mWh cm −3 . Abstract : A membrane‐like flexible supercapacitor with an rGO‐TiO2 /GO/rGO‐TiO2 sandwich structure is prepared by step‐by‐step filtration of GO‐TiO2 mixture dispersion and graphene oxide (GO) dispersion, with the subsequent UV irradiation. The as‐prepared membrane shows high flexibility as an integrated supercapacitor, in which the rGO‐TiO2 layer is used as the active material and the middle GO layer acts as the separator.